An illustrated catalogue of the South American species of the cyphophthalmid family Neogoveidae (Arthropoda, Opiliones, Cyphophthalmi) with a report on 37 undescribed species - Benavides, Ligia; Giribet, Gonzalo (Zootaxa, 2007)
We provide an illustrated catalog of the cyphophthalmid diversity of the Neotropics, including photographs of the holotypes and paratypes (when available) for all but one described South American Neogoveidae. These include the single species of Huitaca, two of the three Metagovea species, the four Neogovea species and ? Gen. enigmaticus. Furthermore we provide collecting data for 37 undescribed species of south American Neogoveidae, including Huitaca (8 spp.), Neogovea (12 spp.) and Metagovea (17 spp.). Distributional data of the species of Neogoveidae add the first records for French Guiana, Peru, Suriname, Trinidad and Tobago, and Venezuela. Colombia shows the largest diversity of Cyphophthalmi among South American countries, perhaps due to the large amount of ecosystems found in this country, but this could also reflect sampling effort.